Mapping the transit network of greater Cartagena with mobile phones: Coverage, accessibility, and informality (2022)
Emerging methods enable researchers and citizens to map transit networks through participatory processes to understand travel patterns, the location of formal and informal transit networks, and the geography of origin and destination points within urban areas. In this paper, we provide a detailed description of the method applied to map the formal and informal urban transit network of the metropolitan area of Cartagena, Colombia. A basic mapping of the entire network at the metropolitan level examines relationships between urban growth and transit supply. We converted the transit data into a static GTFS feed to calculate the coverage and accessibility of the mapped systems. To assess coverage, we compared the percentage of the urban areas served by formal, semi-formal and informal transit. To measure accessibility, we calculated the percentage of population and jobs that can be reached by each transit system from every location in the metropolitan area within four timeframes. Our analysis indicated transit deserts, mostly urban peripheries, which exclude disadvantaged groups from social and professional opportunities. We share the innovations developed and lessons we learned to facilitate transit mapping in other cities with high levels of informal transit. Our static GTFS data adds to a growing repository of open transit data sources that engage citizens, empower researchers, and inform public policy.